Programa psicoeducativo para mejorar la calidad de vida de los cuidadores de pacientes con la enfermedad de Alzheimer (2022)
The general objective of the present study was to design a psychoeducational program that will help improve the quality of life of caregivers of patients with Alzheimer’s disease. Taking into account the results of the participants who were 10 caregivers of the city of Ibague. A descriptive design was used. The evaluation instruments used were instruments to measure quality of life (QOL), Zarit overload scale, Beck depression and anxiety inventory. It was possible to show the effects of most present caregivers highlighting the psychological, overload, anxiety and a perception of poor quality of life.